Synthesis of layered double hydroxides containing Mg2+, Zn2+, Ca2+ and Al3+ layer cations by co-precipitation methods—A review - Theiss, Frederick L.; Ayoko, Godwin A.; Frost, Ray L. (Applied surface science, 2016)
[Display omitted] A flow chart for a simple co-precipitation at variable pH synthesis. Ageing, collection and washing steps have been omitted for clarity. •This review aims to introduce co-precipitation to newcomers to the topic.•The synthesis of LDHs by co-precipitation has been reviewed.•LDHs containing Mg2+, Zn2+, Ca2+ and Al3+ are used as examples.•Hydrothermal synthesis/treatment and the urea method are reviewed.•These techniques have been compared to conventional co-precipitation. Co-precipitation is a common method for the preparation of layered double hydroxides (LDHs) and related materials. This review article is aimed at providing newcomers to the field with some examples of the types of co-precipitation reactions that have been reported previously and to briefly investigate some of the properties of the products of these reactions. Due to the sheer volume of literature on the subject, the authors have had to limit this article to the synthesis of Mg/Al, Zn/Al and Ca/Al LDHs by co-precipitation and directly related methods. LDHs have been synthesised from various reagents including metal salts, oxides and hydroxides. Co-precipitation is also useful for the direct synthesis of LDHs with a wide range of interlayer anions and various bases have been successfully employed to prepare LDHs. Examples of other synthesis techniques including the urea method, hydrothermal synthesis and various mechanochemical methods that are undoubtedly related to co-precipitation have also been included in this review. The effect of post synthesis hydrothermal has also been summarised.